KEMANDIRIAN PETERNAK JANGKRIK DALAM UPAYA MENINGKATKAN EKONOMI DI KELURAHAN LOROK PAKJO KOTA PALEMBANG - Akbar Cahya Romadhon; Eni Murdiati; Muslimin (Lembaran Masyarakat: Jurnal Pengembangan Masyarakat Islam, 2023)
Improving the community's economy aims to improve the standard of living of the community so that they can live prosperously, safely and prosperously. This is certainly very useful for the community so that they can always be in harmony and peace. Through the process of community empowerment, namely Community empowerment aims to empower people in the community to realize the full potential of their skills. The society in question is a society where no one is unproductive or unemployed. Unemployment is a situation where members of the labor force do not have a job and are not currently actively looking for it. Unemployment can be overcome, one of which can be done through community empowerment by developing a cricket livestock business. With cheap and easy costs, crickets are the right choice for people to improve their economy so they can always live safely and prosper.